Analysis of the Effect of Varying Slice Thickness on Image Quality in CT Scans of the Brain With Clinical Infarction at Siti Rahmah Islamic Hospital in Padang - Wahdini Hanifah; Nerifa Dewilza; Sagita Yudha; Livia Ade Nansih; Santa Mareta; Rina Astuti (Archipel: Journal of Indonesian Interdisciplinary Studies, 2026)
An Analysis Of The Effect Of Slice Thickness Variation On Image Quality In Ct-Scan Examination Of The Brain With Clinical Infarction At Siti Rahmah Islamic Hospital In Padang. Infarction stroke occurs when blood flow in the brain is disrupted, causing damage to brain tissue. The appropriate slice thickness increases picture quality and allows for more accurate detection of infarction stroke, reducing the possibility of error. The purpose of this study is to investigate the influence of slice thickness variation on image quality in a brain CT-scan examination with clinical infarction performed at RSI Siti Rahmah Padang. This study was carried out at the RSI Siti Rahmah Padang radiology installation in May-June 2024 utilizing an experimental quantitative research design and a purposive sample technique. Five CT-Scan infarction pictures were taken with a slice thickness of 5 mm and reconstructed to 2 mm and 3 mm. The reconstruction result is then in the ROI on the radiant dicom, then the CNR and SNR calculations are carried out and analysed using SPSS with the Manova test. The result of the slice thickness variation value towards CNR and SNR that has been processed using the Manova test obtained R square CNR 0.839 and SNR 0.797 with a significance level of p of 0.000<0.05, then it was concluded that the slice thickness variation had an effect on the CNR and SNR values. The highest mean value that is optimally meaningful is obtained at a slice thickness of 5 mm, so it can be concluded that the size of the slice thickness is directly proportional to the increase in CNR and SNR values.